DISKRIMINASI ANTARA ANAK LAKI-LAKI DAN PEREMPUAN: STUDI KASUS PADA PENGELUARAN RUMAH TANGGA DI INDONESIA DENGAN MENGGUNAKAN DATA IFLS - Saputra, Andre; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
The rapid development of globalization era led to the emergence of various movements including the movement of women's emancipation that is about gender equality. This research aims to analyze the household expenditure gap between men and women in Indonesia with secondary data from the publication of the Central Bureau of Statistics and IFLS data.   IFLS data used is used from 1997 to 2014. Anal y sis will be done by using the calculation of discrimination with Stata application. The results showed that the pattern of public expenditure for the cost of education of children IFLS 2 until IFLS 5 continues to increase. Education expenditures of children by sex in Indonesia show there is a difference in educational expenditures between boys and girls from year to year (IFLS2 until IFLS 5). Based on urban villages indicating that there is a general difference in educational expenditures of children for rural and urban areas (IFLS 2 to IFLS 5. Comparison of educational expenditure of boys and girls by region shows that are difference in educational expenditure between boys and girls in Sumatra, Java-Bali and Kalimantan, due to differences in economic, social and cultural development prevailing in each region.